Strategi Edukasi Pemberian Makanan Pendamping ASI (MPASI) yang Tepat melalui Pendekatan Multi Media di Wilayah Kerja Puskesmas Sentolo II: Edukasi multi-media, Praktik pemberian MPASI tepat gizi - Telaumbanua, May Kristina Indah K; Setya Wardani, Diadjeng; Aisyah Ardiana, Hanida; Retnaningtyas, Nining; Sinta Devi, Nabila; Widya Risanti, Arini; Permata Sari, Hannie; Emiliana, Farica; Dini Syarafina, Hafizahah (Politeknik Negeri Jember, 2025)
Child malnutrition remains a pressing challenge in Indonesia, including in the catchment area of Sentolo II Health Center, Kulon Progo. In 2025, despite high coverage of child weighing (D/S 88.8%), only 50.88% of children gained weight (N/D), falling below the national target of 60%. Suboptimal complementary feeding (CF) practices, particularly in terms of dietary quality and limited family involvement, were identified as contributing factors. This community service introduced the SEKAR MPASI program (Srawung Edukasi Keluarga lan Anak Remen MPASI), a multi-media nutrition education strategy combining short recipe videos, an illustrated booklet with QR codes, interactive “Ngobrol Pawon” discussions, and local complementary feeding competitions. Evaluation showed a marked improvement in maternal knowledge (post-test scores increased from 82 to 97), stronger family engagement, and competition participation exceeding targets. The program demonstrates that participatory, culturally rooted multimedia education can effectively improve complementary feeding practices and is feasible for integration into routine posyandu activities. Keywords: complementary feeding; multimedia education; posyandu; behaviour change; child nutrition